2021
DOI: 10.48123/rsgis.983251
|View full text |Cite
|
Sign up to set email alerts
|

3D Dense Reconstruction of Road Surface from UAV Images and Comparison of SfM Based Software Performance

Abstract: Unmanned Aerial Vehicle (UAV) technology is one of the fastest-growing technologies especially used in image processing. Structure-from-Motion (SfM) based software are usually used to convert two-dimensional UAV-based images into three-dimensional (3D) data. Then, objects such as buildings, trees, and roads can be classified from the 3D data for further analysis. In this study, the road surface generated from 3D data was evaluated. There are several factors that affect the accuracy of the 3D data. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The combination of GPR, RM and IRT allowed the collection of detailed internal data on the exact nature and extent of the defects, and the overall condition of the examined heritage. Typically, single NDT procedures are used, but the current study clearly shows the benefits of integrating methods and the combined use of multiple techniques in maximizing data, both quantitatively and qualitatively (Sbartaï et al, 2007;Pellicer and Gibson, 2011;Fernandes et al, 2015;Zeybek and Biçici, 2020;Biçici and Zeybek, 2021;Zeybek and Biçici, 2021).…”
Section: Discussionmentioning
confidence: 83%
“…The combination of GPR, RM and IRT allowed the collection of detailed internal data on the exact nature and extent of the defects, and the overall condition of the examined heritage. Typically, single NDT procedures are used, but the current study clearly shows the benefits of integrating methods and the combined use of multiple techniques in maximizing data, both quantitatively and qualitatively (Sbartaï et al, 2007;Pellicer and Gibson, 2011;Fernandes et al, 2015;Zeybek and Biçici, 2020;Biçici and Zeybek, 2021;Zeybek and Biçici, 2021).…”
Section: Discussionmentioning
confidence: 83%
“…LiDAR sensors have a high resolution and accuracy when measuring objects [66] and represent a promising technology for road maintenance in the near future [67]. Zeybek and Bicici [68] have shown that LiDAR sensors can detect deformations on the road surface. This 3D sensor technology will revolutionize measurement methods, offering high-density data and visualizations for small-scale projects.…”
Section: Introductionmentioning
confidence: 99%
“…One widely used technology is the mobile laser scanning (MLS) system [12,13]. Additionally, unmanned aerial vehicles (UAVs) have recently become a popular technology for this purpose [14][15][16]. In this technology, images collected from UAV flights are converted into 3D data using photogrammetry technology [17].…”
Section: Introductionmentioning
confidence: 99%